The relationship between moral sensitivity and caring behavior among nurses in iran during COVID-19 pandemic - Fatemeh Hajibabaee; Waliu Jawula Salisu; Elham Akhlaghi; Mansoureh Ashghali Farahani; Maryam Mohamadzadeh Nojeh Dehi; Shima Haghani (BMC, 2022)
Abstract Background Caring for patients during a pandemic can be difficult for healthcare workers, the patients themselves, and healthcare systems. Nurses are expected to recognize ethical dilemmas and make sound judgments when confronted with them. Sensitizing nurses to ethical issues strengthen their ability to identify ethical dilemmas and make ethical choices. As a result, this study aimed to determine a relationship between moral sensitivity and caring behavior among nurses during the coronavirus (COVID-19) pandemic. Method The current study is a cross-sectional study of 406 nurses who worked in a single hospital during the COVID-19 epidemic. We used a demographic questionnaire and the caring behavior inventory (CBI) tool to collect data online. The data were analyzed using descriptive and correlational statistics. Findings Eighty-three point seven percent of participants in this study were female, and 71.9% were married. 47.5% reported caring for a COVID-19 patient for longer than a month; their average work experience was 13.1 years. Additionally, Moral Sensitivity correlated positively with caring behavior and its dimensions (r = 0.164, P = 0.001). However, a significant and inverse link existed between the dimension "following the rules" and the nurse's caring conduct (r = -0.117, P = 0.019). Conclusion During the pandemic, nurses' moral sensitivity was moderate and significantly connected with their caring behavior. Because nurses encounter numerous obstacles while caring for patients in critical conditions, they require ethical empowerment to perform correctly, as caring behavior improves with increased moral sensitivity.